The psycholinguistic approach to unity and diversity - Leonor Scliar Cabral (Ilha do Desterro)
Some aspects of contemporary communication regarding unity and diversity will be examined as follows. On the one hand, globalization provided mainly by mass media, particularly by Internet and the on line electronic mail, will be scrutinized in relation to its psycholinguistic consequences: What are the differences that appear in human processing and how is the logical distinction between unity and diversity faced? How deep are the changes experienced by children, who are acquiring and learning their oral and written languages, using such media? On the other hand, despite globalization, the geometrical growth of science and technology brings with it a parallel lexical explosion: specific texts undermine the possibility of their comprehension by the outsider as if the text was written in a foreign language, and so, the unity of communication is broken and distortions may appear.